Il farmaco ricerca, sviluppo e applicazione in terapia - Giacomo Capone (Phármakon, 2019)
"The drug: research, development and application in therapy" is an in-depth study on the Research and Development process that a drug performs from the moment it is designed up to its practical use. When a molecule is considered suitable for a medicine, a long process is activated which has as its goal the creation of a new therapeutic tool and its approval for marketing. A path marked by the strict observance of regulations and laws that have evolved over time in step with scientific and technological progress. A path that however has often been determined also by tragic events following damaging adverse reactions that have triggered processes of revision of the norms and experimental protocols. This book starts with a summary on the history of Western pharmacology, written to allow the reader to understand the circumstances that have been the background to those dynamics through which the Research and Development process has gradually consolidated. An important part of the book is dedicated to some aspects that are crucial in the normative universe in which the drug is placed, such as the advanced therapies and new approaches for clinical research. The authors also focused on the prescriptions of off-label drugs and on the issues of pharmacoutilization and pharmacovigilance, two disciplines that, in a few years, have become increasingly influential in the present and future perspectives, not only of the pharmaceutical sciences but of the entire society.